Menyadarkan Homo Economicus: Tilikan Psiko-ekonomi Islam dalam Paradigma Attasian - Sandimula, Nur Shadiq; Syarifuddin, Syarifuddin (ITB AAS INDONESIA Surakarta, 2024)
This study aims to critically examine the concept of Homo Economicus which is postulated in conventional economics disciplines, in the light of the Islamic Psycho-economic perspective based on the Attasian paradigm. The research used qualitative library research descriptively with a content analysis approach. The primary data sources are the works of Syed Muhammad Naquib al-Attas whose contents are relevant to the object of study. The results of this study indicate that Homo Economicus is an economic agent that rises from the ideas and experiences of Western civilization and has the personality of al-nafs al-ammarah. Rationality and rational choices are based on self-interest, encapsulated in the paradigm of atomistic individualism and egoistic utilitarianism. The social ethos adopted by Homo Economicus is based on material values that bear consumerism lifestyle and antagonism among other human beings. In contrast, Islam postulates an economic agent as a religious personality who has reached the level of al-nafs al-muthmainnah, has moral and social sensitivity, and aims at the common good of every economic activity.